RUSSIA AND GEORGIA: POST-SOVIET METAMORPHOSES OF MUTUAL RELATIONS - MATSABERIDZE, Malkhaz (CENTRAL ASIA AND THE CAUCASUS, 2008)
The post-Soviet relations between Russia and Georgia are best described as complicated and contradictory. Indeed, the less than two decades of post-Soviet history include several different but logically connected periods. This means that anyone wishing to better understand the nature of the relations between the two countries and the meaning of their current stage should grasp their logic. Put in a nutshell it means that Russia still hopes to preserve the tools of its influence on Georgia, while Georgia is seeking a civilized model of relations with Russia. Georgian officials describe it as respect for Russia’s “legal interests "in the region and protection of Georgia’s nation-al and state interests. Georgia’s official position expounded be-low, with which the present author agrees, is open for discussion. By the late 1980s the national-liberation movement had created a context in which it became clear that Georgia should restore its state independence; this meant that Moscow was expected to recognize the fact of occupation and annexation of Georgia and that the international community should help Georgia overcome their negative repercussions. During Gorbachev’s perestroika, when the Soviet regime became slightly more liberal than before, the Georgians awakened to their past. The Georgian Democratic Republic (1918-1921) was the object of numerous publications in Georgian non-official periodicals that stirred up the idea of restored in-dependence; on many occasions the public agreed on the nature of a future independent Georgian state. Under the agreement of 7 May, 1920 the Russian Soviet Federative Socialist Republic recognized the independence of the Georgian Democratic Republic. Some time later the Red Army attacked Georgia, occupied the country after a short war in February-March 1921, and established Soviet pow-er. Later Soviet Georgia was incorporated into the Soviet Union. Much has been already written about these events.1 Georgia tried to restore its independence through talks with Russia on the strength of the developments of 1920-1921. It was expected that Russia would recognize the fact of Georgia’s occupation and annexation by the Red Army and of Georgia’s incorporation into the Soviet Union against its will. This recognition should have been accompanied by liquidation of the results of ag-gression and restoration of Georgia’s state independence. The victory of Zviad Gamsakhurdia’s Round Table—Free Georgia Bloc at the parliamentary elections of 28 October, 1990 shifted the idea into the sphere of practical policy: after coming to pow-er the new president officially announced that the country had entered a period of transition toward restored independence.2 Moscow never responded to Tbilisi’s demands to recognize the facts of occupation and annexation; the Soviet government, which refused to recognize Georgia’s independence in principle, was building up tension in the country.3 The Decision of the Supreme Soviet of the U.S.S.R. on the referendum on the Soviet Union’s continued existence scheduled for17 March, 1991 quenched the hopes that the Soviet leaders would admit the facts of aggression and annexation.